WHO MAKES ADOLESCENTS HAPPY? AN EXPLORATIVE STUDY USING THE INDIGENOUS PSYCHOLOGY APPROACH - Hamka, Annisa Soleha; Yuniarti, Kwartarini Wahyu; moordiningsih, Moordiningsih; Kim, Uichol (Indigenous, 2015)
This study is aimed at discovering who the source of happiness is for adolescents and how he or she accomplishes his or her role in creating happiness. A number of 458 senior high school students completed an open-ended questionnaire developed by Kim and Park (2008). An indigenous approach is used to analyse respondentsâ answers to the open-ended questionnaire. A categorization of respondentsâ answers and cross tabulation is also conducted. Analysis results show that a majority of adolescencesâ source of happiness derives from the family (50.1%), and friends (27%). Their role in creating happiness was by supporting (54.3). Acceptance of adolescents (20.8%) was also a source of happiness for adolescents. Providing facilities and prayers was also a role given for adolescents.